Vibration Detection of the Electrical Motors using Strain Gauges. (2016) - Ágoston, Katalin
Abstract: This paper presents some aspects regarding to vibration measurement using strain gauge sensors. Mechanical faults, usages, or electrical faults, can be detected through noises and/or vibrations which have different amplitude and frequency against the normal sound of the induction motor. Different vibration transducers can be used for noise and vibration measurements with fault detection purpose. The conditioning circuit of the vibration transducers can be resistive type also and in this case the vibration is converted into a variation of resistance (strain gauges). From resistance variation of the strain gauges a voltage variation can be obtained with proper conditioning circuit. This voltage is measured and analyzed to obtain the vibration components. The amplitude and frequency of the vibration are changing when the functioning conditions of the machine are changing. It is important to determine the harmonic spectra of the vibration for different faults and to compare with the spectra corresponding to the normal functioning of the electrical motor. Two virtual instruments were developed in LabView and LabWindows/CVI to measure and analyze the vibration. Using the virtual instruments the acquired signal was analyzed and the vibration characteristics and spectra were studied in different cases. It is shown through simulations and measurements for a small electrical motor that the weak base influences the amplitude of frequency components of the harmonics spectra.